GROUP METAPHOR AS A TOOL FOR COHESION OF THE GROUP FORMATION - Церковний, Альберт Олександрович; Церковна, Маріанна Вікторівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article deals with the formation of group cohesion in students during training. The authors consider the problem of ﬁ nding a tool to enhance the process of group cohesion formation within the educational training program. The authors suggest the use of metaphor in a group within the academic training program. Group metaphor created by all participants of the training, is used as an instrument for the formation of group cohesion.